Upregulation of sICAM-1 and sVCAM-1 Levels in the Cerebrospinal Fluid of Patients with Schizophrenia Spectrum Disorders - Meixensberger, Sophie; Kuzior, Hanna; Fiebich, Bernd L.; Süß, Patrick; Runge, Kimon; Berger, Benjamin; Nickel, Kathrin; Denzel, Dominik; Schiele, Miriam A.; Michel, Maike; Maier, Simon; Bechter, Karl; et al. (Diagnostics (Basel), 2021)
Immunological explanatory approaches are becoming increasingly important in schizophrenia research. In this context, the function of the blood-brain barrier (BBB) and the blood-cerebrospinal fluid (CSF) barrier (BCSFB) plays an essential role. Different adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), are key elements in sustaining the integrity of the BBB and BCSFB. The objectives of this study were to (1) compare the levels of different cell adhesion molecules in the CSF of patients with schizophrenia spectrum disorders to those of patients with unipolar depression and (2) analyze their association with the established markers of the BBB/BCSFB function (CSF total protein and albumin quotient (AQ)). Therefore, a total of 40 patients with schizophrenia spectrum disorder and 39 age- and sex-matched control patients with unipolar depression were analyzed. The levels of soluble ICAM-1 (s-ICAM-1), soluble VCAM-1 (s-VCAM-1), and plasminogen activator inhibitor 1 (PAI-1) in the CSF were measured using a magnetic bead multiplexing immunoassay. The levels of sICAM-1 (p < 0.001), sVCAM-1 (p < 0.001), and PAI-1 (p < 0.001) in the CSF were significantly higher in patients with schizophrenia spectrum disorder than in patients with unipolar depression. In addition, a significant correlation of sVCAM-1 levels with total protein concentrations (r = 0.454, p = 0.003) and AQ levels (r = 0.512, p = 0.001) in patients with schizophrenia spectrum disorders was observed. The results revealed that sICAM-1 and sVCAM-1 levels in the CSF were higher in patients with schizophrenia spectrum disorder than in those with depression. These circulating signaling molecules may indicate endothelial dysfunction causing impaired BBB/BCSFB function in patients with schizophrenia spectrum disorders. Consistent with this view, a highly significant correlation of sVCAM-1 with CSF protein and AQs was detected. Upregulation of these cell adhesion molecules might be indicative of a proinflammatory immune response underlying the BBB/BCSFB disturbance in a subgroup of patients with schizophrenia spectrum disorders. The significance of the study is limited by its retrospective research design and by the absence of a healthy control group. The assay used was not previously established for the measurement of CSF. Further translational and controlled studies of the role of different cell adhesion molecules in schizophrenia are needed.